Effects of some plant growth stimulants on yield and yield components of wheat (Triticum aestivum L., Narin cultivar) under saline condition - Mirzapour, Mohammad Hadi; Nourgholipour, Fereydoun; Ja’farnezhadi, Ali Reza (Journal of Cereal Research, 2022)
In recent years, spreading environmental stresses such as salinity have had a significant impact on the quantitative and qualitative of agricultural products. In order to investigate the effects of using some plant growth stimulants to improve growth and yield of wheat in saline condition, this experiment was conducted with seven treatments including 1-control (application of chemical fertilizer based on soil test) 2- first treatment + soil application of 5 kg.ha-1of humic acid3- first treatment + spraying amino acidsin 5 gr.lit-1 4- first treatment + seed priming of Azotobacter with a concentration of 1% 5- first treatment + foliar application of fulvic acid in 5 gr.lit-1 6- first treatment + foliar applying seaweedin 5 gr.lit-1 and 7- combined treatment (1+2+3+4+5+6) in a randomized complete blocks design in three replications and at two years (2017-2019) in Qom province. The biennial results showed highest seed, straw and biological yield of wheat were obtained in treatment seven, which had a significant difference with another stimulant and control and with 3194, 4993 and 8187 kg.ha-1, respectively which was 35%, 25% and 30% higher than control. Also, the yield trait, such as plant height, cluster length and tillers plant-1 were the highest in this treatment. It seems that the combined use of growth stimulants had a significant effects on yield and some yield traits of wheat in saline conditions and it is suggested to investigate the effects of these stimulants in combination with 50 and/or 70% out of the recommended fertilizers and as well as the time of applying these stimulants.